Constrictive Pericarditis after Open Heart Surgery: A 20-Year Case Controlled Study. (15th April 2021) - Moreyra, Abel E.; Cosgrove, Nora M.; Zinonos, Stavros; Yang, Yi; Cabrera, Javier; Pepe, Russell J.; Alam, Amit; Kostis, John B.; Lee, Leonard; Kostis, William J.; ,
Abstract: Background: Constrictive pericarditis is a rare complication of open heart surgery (OHS), but little is known regarding the etiologic determinants, and prognostic factors. The purpose of this study was to investigate clinical predictors and long term prognosis of post-operative constrictive pericarditis (CP). Methods: Using the Myocardial Infarction Data Acquisition System database, we analyzed records of 142, 837 patients who were admitted for OHS in New Jersey hospitals between 1995 and 2015. Ninety-one patients were hospitalized with CP 30 days or longer after discharge from OHS. Differences in proportions were analyzed using Chi square tests. Controls were matched to cases for demographics, surgical procedure type, history of OHS, and propensity score. Cox proportional hazard models were used to evaluate the risk of all-cause death. Log-rank tests and Cox models were used to assess differences in the Kaplan-Meier survival curves with and without adjustments for comorbidities. Results: Patients with CP were more likely to have history of valve disease (VD, p < 0.001), atrial fibrillation (AF, p = 0.024) renal disease (CKD, p = 0.028), hemodialysis (HD, p = 0.008), previous OHS (p < 0.001). Patients with CP compared to matched controls had a higher 7-year mortality (p < 0.001). This difference became statistically significant at 1-year after surgery. Conclusion: CP is a rare complication of OHS that occurs more frequently in patients with VD, AF, CKD, HD, multiple OHS, and it is associated with an unfavorable long-term prognosis. Given the large number of OHS performed every year, the results highlight the need for clinicians to recognize and properly manage this complication of OHS. Highlights: Constrictive pericarditis after open heart surgery, is a rare complication, albeit with an unfavorable long-term prognosis. It occurs more frequently in patients with multiple cardiac surgeries, atrial fibrillation, and chronic renal disease. The number of open heart surgeries yearly highlights the need to recognize and properly manage this complication. This is the first case-controlled study of patients with constrictive pericarditis after open heart surgery.